Molecular detection of Hsp90 inhibitor suppressing PCV2 replication in host cells. (July 2019) - Liu, Jie; Ma, Chang; Zhang, Xuliang; You, Jinwei; Dong, Min; Chen, Li; Jiang, Ping; Yun, Shifeng
Abstract: Porcine Circovirus Type 2 (PCV2) is a pathogen that has the ability to cause devastating disease manifestations in pig populations with major economic implications. Our previous research found that Hsp90 is required for PCV2 production in PK-15 and 3D4/31 cells. The aim of this study was to evaluate the effect of Hsp90 inhibitor regulating PCV2 replication and to explore its underlying mechanism. In PK-15 and 3D4/31 cells treated with 17-AAG after viral adsorption, replication of PCV2 was attenuated as assessed by quantitating the expression of viral protein. Following NF-κB activation it was observed that 24hpi with PCV2 was significantly inhibited in the presence of 17-AAG. The expression of Hsp90 associated client proteins in PCV2-infected cells were also reduced in the presence of 17-AAG. However, treatment with MG-132 failed to rescue 17-AAG mediated reduction of PCV2 production in host cells. Thus, Hsp90 regulates PCV2 by modulating cellular signaling proteins. These results highlight the importance of cellular proteins during PCV2 infection and the possibility of targeting cellular chaperones for developing new anti-rotaviral strategies. Highlights: 1. Hsp90 inhibitor(17-AAG) could inhibit the replication of PCV2 in the PK-15 and 3D4/31 cells. 2. 17-AAG could inhibit NF-κB activation induced by PCV2 infection. 3. 17-AAG reduced the expression of Hsp90 associated client proteins in PCV2-infected cells. 4. Proteasomal degradation does not involve in PCV2 inhibition by 17-AAG.